Attribution Analysis of Runoff Variability in Northern-Huai River Plain Based on Improved Budyko-Fu Equation - LIU Kailei; WANG Yining; LI Rui (Renmin Zhujiang)
The surface water resources in plain areas are affected by a combination of factors such as precipitation and groundwater exploitation, leading to complex transformations and water cycles. Issues like insufficient water resource security capacity and competition for water among different sectors are common. This study is carried out in the Northern Huai River Plain. This study introduces an effective rainfall indicator with an emphasis on improving the annual-scale Budyko-Fu (BF) water-heat balance equation. Subsequently, the elasticity coefficient method is used to quantitatively evaluate the response sensitivity and contribution of precipitation, phreatic evapotranspiration, and other factors to the variation in surface water resources. The results show that the root mean square error of the evapotranspiration series simulated by the improved equation of water and heat balance (BF-NH) in the Northern Huai River Plain is about 50% lower than that of the BF equation, which can more accurately describe the influence of rainfall and other factors on the regional actual evapotranspiration. From 1956 to 2021, the runoff depth increased slowly with the increase in regional rainfall and the decrease in evapotranspiration of soil phreatic water, and the annual growth rate was about 0.40 mm/a. Regional precipitation, phreatic evapotranspiration, and water storage contribute 73.1%, 19.9%, and 7.0%, respectively, indicating that regional precipitation is the main factor affecting runoff variation in the Northern Huai River Plain.